Frameworks for ICT policy : government, social and legal issues - Adomi, Esharenana E. (Information Science Reference, 2011)
"This book provides policy-relevant insights and information to aid those engaged in systematic research and teaching about ICT policy formation and implementation"--Provided by publisher
"Premier reference source."--Cover
Keywords: Computer crimes -- Prevention -- International cooperation; Information technology -- Government policy -- Cross-cultural studies; Information technology -- Security measures -- Cross-cultural studies